Analysis and advanced characterization of municipal solid waste vermicompost maturity for a green environment. (1st February 2020) - Srivastava, Vaibhav; Goel, Gaurav; Thakur, Vijay Kumar; Singh, Rajeev Pratap; Ferreira de Araujo, Ademir Sergio; Singh, Pooja
Abstract: Rapid demographic expansion along with increasing urbanization has aggravated the problem of solid waste management. Therefore, scientists are seeking waste management methods that are eco-friendly, cost effective and produce immediate results. In the developing world, municipal solid waste (MSW) contains mostly organic substances, therefore vermicomposting could be a better and cost-effective option for waste management. In this study, vermicomposting of organic portion of MSW with cow dung (additive) was performed using Eisenia fetida . The results showed significant ( p < 0.001) decline in pH (13.17%), TOC (21.70%), C: N (62.53%) and C: P (57.66%) ratios, whilst total N (108.9%), P (84.89%) and K (21.85%) content increased ( p < 0.001) in matured vermicompost. Different enzymatic activities declined during termination phase of vermicomposting experiment with maximum decrease of 41.72 ( p = 0.002) and 39.56% ( p = 0.001) in protease and β-glucosidase, respectively. FT-IR, TGA, DSC and SEM studies suggested that final vermicompost was more stabilized as compared to initial waste mixture, characterized by reduced levels of aliphatic materials, carbohydrates and increase in aromatic groups possibly due to biosynthesis of humic substances. Both, the conventional (physicochemical and enzyme activity) and advanced techniques depict maturity and stability of the ready vermicompost. However, FT-IR, TGA, DSC and SEM were proved to be more promising, fast and reliable techniques over conventional analyses. Graphical abstract: Image 1 Highlights: Vermicomposting of organic portion of MSW was successfully performed. Physico-chemical and enzyme activity analyses were done (conventional techniques). Maturation study of vermicompost (VC) was performed using FTIR, TGA, DSC and SEM. MSW (organic part) could be utilized for nutrient recovery through vermicomposting.